PENCIPTAAN KARYA PAKELIRAN SAJAK "GEDOG GERODOG" - Bayu Senopati, I Gusti Agung; Sidia, I Made; Gumana Putra, I Gusti Ngurah (JURNAL DAMAR PEDALANGAN, 2025)
The final project script of the Independent Study Project was conducted for one semester at the Sanggar Seni Hari Dwipa Gamelan Group, with the aim of creating a Balinese puppetry art work called Pakeliran Sajak Gedog Gerodog, which raises the phenomenon of Gedog Gerodog in the world of Balinese puppetry. This final project research uses a combination research method, namely quantitative research method and qualitative research method, with data collection through interviews and observations. The results of the study show that Gedog Gerodog is a phenomenon that is mystical and realistic, which occurs because puppets are starting to be forgotten in modern times as a means of worship. The Pakeliran Sajak Gedog Gerodog artwork creates a new concept in the world of puppetry, by combining poetry and puppetry, using the Panca Sthiti Ngawi Sani method, which includes Ngawi Rasa (Inspiration Stage), Ngawacak (Exploration Stage), Ngarencana (Conception Stage), Ngawangun (Execution Stage), and Ngebah (Performance Stage). This concept enables a more dynamic and interactive puppet performance. The Pakeliran Sajak Gedog Gerodog artwork also has educational value, as it can be a means to introduce and preserve Balinese puppetry culture. In addition, this artwork can also be an inspiration for other artists and researchers to develop innovative and creative art works.